PENGARUH INTELLECTUAL CAPITAL, GOOD CORPORATE GOVERNANCE, DAN REPUTASI PERUSAHAAN TERHADAP NILAI PERUSAHAAN SEKTOR CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sylvia Putri Permatasari (Accounting Study Program, Universitas Ciputra Surabaya, 2023)
In 2018 and 2019 the stock index of the consumer goods sector continued to decline, which means the average share price of this sector decreased. Stock prices can represent investors’ opinions about the value of the company. Consumer goods sector companies have a lot of human re- sources (HR) so that it can be an advantage to create added value for the company if it can be managed properly. HR management can be measured using IC. In addition to human resources, corporate governance is also one of the important things in the company and can provide added value. There are several things that can measure a company’s GCG. Two of them are the proportion of independent commissioners and the number of audit com- mittees. Company reputation is also important for companies listed on the Indonesia Stock Exchange. The reputation of the company is one thing that should be maintained because it also affects the value of the company. One way to measure reputation is by getting awards such as the Corporate Image Award. This study aims to determine the effect of intellectual capital, good corporate governance, and company reputation on firm value. The sample in this study are companies listed in the consumer goods sector listed on the IDX for the period 2018–2019. This study uses purposive sampling as a data collection technique. The data analysis used in this research is the clas- sical assumption test and multiple linear regression analysis. The results of this study state that intellectual capital, good corporate governance, and company reputation have no effect on firm value.